A Traditional Chinese Medicine Xiao-Ai-Tong Suppresses Pain through Modulation of Cytokines and Prevents Adverse Reactions of Morphine Treatment in Bone Cancer Pain Patients - Yan Cong; Kefu Sun; Xueming He; Jinxuan Li; Yanbin Dong; Bin Zheng; Xiao Tan; Xue-Jun Song (Mediators of Inflammation)
Treating cancer pain continues to possess a major challenge. Here, we report that a traditional Chinese medicine Xiao-Ai-Tong (XAT) can effectively suppress pain and adverse reactions following morphine treatment in patients with bone cancer pain. Visual Analogue Scale (VAS) and Quality of Life Questionnaire (EORTC QLQ-C30) were used for patient’s self-evaluation of pain intensity and evaluating changes of adverse reactions including constipation, nausea, fatigue, and anorexia, respectively, before and after treatment prescriptions. The clinical trials showed that repetitive oral administration of XAT (200 mL, bid, for 7 consecutive days) alone greatly reduced cancer pain. Repetitive treatment with a combination of XAT and morphine (20 mg and 30 mg, resp.) produced significant synergistic analgesic effects. Meanwhile, XAT greatly reduced the adverse reactions associated with cancer and/or morphine treatment. In addition, XAT treatment significantly reduced the proinflammatory cytokines interleukin-1β and tumor necrosis factor-α and increased the endogenous anti-inflammatory cytokine interleukin-10 in blood. These findings demonstrate that XAT can effectively reduce bone cancer pain probably mediated by the cytokine mechanisms, facilitate analgesic effect of morphine, and prevent or reduce the associated adverse reactions, supporting a use of XAT, alone or with morphine, in treating bone cancer pain in clinic.